A lithium-based montmorillonite-coated LiFePO4 core-shell material and its preparation method and application

By covering the lithium -based monatoplera on LIFEPO4 to form a mask -shaped nuclear shell structure, the resistance problem of lithium ion sieve during the electrochemical Li+embedded/removal process, and the lower electrochemical lithium lifting Energy consumption and working voltage.

CN117813408BActive Publication Date: 2025-01-28GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380011985.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-22
Publication Date
2025-01-28
Estimated Expiration
2043-11-22

AI Technical Summary

Technical Problem

During the electrochemical Li+ embed/detachment process, the existing lithium-ion sieve has polarization due to the electrode-solution interface resistance and the electrode itself, resulting in polarization of the Li+ embed/detachment platform, which has a high charge and discharge voltage, and has a relatively high energy consumption of lithium extraction. big.

Method used

Using lithium -based Mongolian stone littering lifpo4 nuclear shell material, by covering lithium -based Mongolian littering on the surface of lifpo4 lithium ion sieve, forming a mask -littering nuclear shell structure, using the type of quality of the mask -shaped layer structure The principle of replacement, improve the LI+conduction capacity and hydrophilicity, and reduce the solid-liquid surface resistance.

Benefits of technology

A significant reduction of the resistivity of the lithium ion screen under the conditions of the water system, improved the conduction capacity between Li+in the water phase-LifePO4 grain, and reducing the working voltage and energy consumption of the electrochemical lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117813408B_ABST
    Figure CN117813408B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of metallurgy technology, and relates to a lithium-based montmorillonite-coated LiFePO4 core-shell material, a preparation method thereof, and an application thereof. The lithium-based montmorillonite-coated LiFePO4 core-shell material comprises LiFePO4 as a core layer and lithium-based montmorillonite as a shell layer, and the lithium-based montmorillonite is coated on the surface of LiFePO4. The lithium-based montmorillonite-coated LiFePO4 core-shell material prepared by the present invention has a high ion conductivity and can make up for the LiFePO4-water interface Li + Defects with large conduction resistance can promote Li + The conduction between the aqueous phase-LiFePO4 grains, that is, the overall resistivity of the slurry is reduced, and the operating voltage is lower, thereby further reducing the energy consumption of electrochemical lithium extraction from salt lakes. The lithium-based montmorillonite-coated LiFePO4 core-shell material prepared in the present disclosure can be widely used in lithium extraction from salt lake brine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metallurgical technology, and in particular to a lithium-based montmorillonite-coated LiFePO4 core-shell material and a preparation method and application thereof. Background Art

[0002] Lithium resources are widely used in lithium-ion batteries and other related fields. With the rapid development of the lithium-ion battery industry, the demand for lithium resources in industrial production has increased faster and faster. In recent years, there has even been a situation where lithium raw materials are in short supply. How to extract lithium from salt lakes efficiently and quickly has always been a scientific problem to be solved. Salt lakes have low lithium content and high content of other metals such as magnesium. Due to the similar properties of magnesium and lithium, it is difficult to selectively extract lithium resources from salt lakes. Compared with traditional methods such as precipitation, calcination and leaching, carbonization, nanofiltration membrane, solvent extraction and adsorption, the electrochemical method of extracting lithium from salt lake brine can achieve the advantages of cleaner, lower energy consumption and higher extraction efficiency.

[0003] The electrochemical method of extracting lithium from salt lake brine is based on the fact that lithium ion sieves can realize redox reactions at different voltages and simultaneously complete Li + The principle of the embedding / extraction process. Existing lithium ion sieve substrates include: spinel LiMn2O4, layered oxide type LiMO2 (M is a transition metal ion, i.e. Ni, Co, Mn, etc.), and polyanion salt LiFePO4. However, the first two are oxides, which usually involve metal ion dissolution processes, resulting in poor substrate life. Therefore, LiFePO4 is most suitable for electrochemical work under aqueous conditions. + The insertion / extraction process will cause Li + There is polarization phenomenon in the insertion / extraction voltage platform (the charging and discharging voltage is higher).

[0004] In view of this, the present disclosure is proposed. Summary of the invention

[0005] The purpose of the present disclosure is to provide a lithium-based montmorillonite-coated LiFePO4 core-shell material and a preparation method and application thereof.

[0006] In order to achieve at least one of the above-mentioned objectives of the present disclosure, the following technical solutions may be adopted:

[0007] In a first aspect, the present disclosure provides a lithium-montmorillonite-coated LiFePO4 core-shell material, which includes LiFePO4 as a core layer and lithium-montmorillonite as a shell layer, and the lithium-montmorillonite is coated on the surface of the LiFePO4.

[0008] In some embodiments of the present disclosure, the mass ratio of the LiFePO4 to the lithium-based montmorillonite is 1:0.1% to 1%.

[0009] In a second aspect, the present disclosure provides a method for preparing a lithium-montmorillonite-coated LiFePO4 core-shell material, which comprises mixing LiFePO4 and lithium-montmorillonite, adding an alcohol solvent, performing a gel reaction, and drying and grinding the obtained gel.

[0010] In some embodiments of the present disclosure, the mass ratio of the LiFePO4 to the lithium-based montmorillonite is 1:0.1% to 1%.

[0011] In some embodiments of the present disclosure, the added amount of the alcohol solvent accounts for 30% to 300% of the mass of the LiFePO4.

[0012] In some embodiments of the present disclosure, the alcohol solvent includes any one of ethanol, ethylene glycol, polyethylene glycol, propanol or methanol, or a combination of at least two thereof.

[0013] In some embodiments of the present disclosure, the temperature of the gel reaction is 70-100°C.

[0014] In some embodiments of the present disclosure, the gel is dried at a temperature of 80 to 120° C. and a drying time of 1 to 18 hours.

[0015] In some embodiments of the present disclosure, the method for preparing the lithium-based montmorillonite comprises: mixing and infiltrating the montmorillonite with a first lithium solution, then filtering and collecting the solid powder, and drying the solid powder.

[0016] In some embodiments of the present disclosure, the lithium ion concentration in the first lithium solution is greater than 1 g / L.

[0017] In some embodiments of the present disclosure, the soaking temperature is 70-100° C., and the soaking time is greater than 12 hours.

[0018] In some embodiments of the present disclosure, the solid powder is dried at a temperature of 80 to 120° C. and a drying time of 3 to 12 hours.

[0019] In a third aspect, the present disclosure provides the use of the lithium-based montmorillonite-coated LiFePO4 core-shell material as described in any of the aforementioned embodiments or the lithium-based montmorillonite-coated LiFePO4 core-shell material prepared by the preparation method of the lithium-based montmorillonite-coated LiFePO4 core-shell material as described in any of the aforementioned embodiments in lithium extraction from salt lake brine.

[0020] In a fourth aspect, the present disclosure provides a method for extracting lithium from salt lake brine, comprising: using the lithium-based montmorillonite-coated LiFePO4 core-shell material as described in any one of the aforementioned embodiments or the lithium-based montmorillonite-coated LiFePO4 core-shell material prepared by the preparation method of the lithium-based montmorillonite-coated LiFePO4 core-shell material as described in any one of the aforementioned embodiments as a lithium ion sieve, denoted as M-LiFePO4, and removing lithium from a portion of the lithium-based montmorillonite-coated LiFePO4 core-shell material to prepare a lithium-poor ion sieve, denoted as M-FePO4;

[0021] The M-LiFePO4 and the M-FePO4 are respectively added into the anode chamber and the cathode chamber for electrochemical lithium extraction;

[0022] or,

[0023] The M-LiFePO4 and the M-FePO4 are coated on the anode plate and the cathode plate respectively for electrochemical lithium extraction.

[0024] In some embodiments of the present disclosure, when the M-LiFePO4 and the M-FePO4 are added to the anode chamber and the cathode chamber respectively for electrochemical lithium extraction, the following operations are included:

[0025] The M-LiFePO4 and the second lithium solution are mixed into a slurry and placed in the anode chamber, and the M-FePO4 and brine are mixed into a slurry and placed in the cathode chamber;

[0026] An anode plate is inserted into the anode chamber, and a cathode plate is inserted into the cathode chamber. The anode chamber and the cathode chamber are separated by an anion membrane. Voltage is applied to the anode plate and the cathode plate to perform electrochemical lithium extraction, and the operation stops when a first cut-off voltage is reached.

[0027] In some embodiments of the present disclosure, the solid-liquid ratio of the M-LiFePO4 and the second lithium solution in slurry preparation is 1:1-30; the solid-liquid ratio of the M-FePO4 and the brine in slurry preparation is 1:1-30.

[0028] In some embodiments of the present disclosure, the anode chamber and the cathode chamber are kept stirred during the lithium extraction process.

[0029] In some embodiments of the present disclosure, the stirring speed is 100 to 1000 r / min.

[0030] In some embodiments of the present disclosure, the main component of the second lithium solution is LiCl, wherein the lithium concentration is <15 g / L.

[0031] In some embodiments of the present disclosure, when the M-LiFePO4 and the M-FePO4 are respectively coated on the anode plate and the cathode plate for electrochemical lithium extraction, the coating thickness of the M-LiFePO4 is 0.01 to 1 cm; the coating thickness of the M-FePO4 is 0.01 to 1 cm.

[0032] In some embodiments of the present disclosure, the anode plate includes one of a graphite electrode, a platinum metal sheet, or a carbon fiber electrode.

[0033] In some embodiments of the present disclosure, the anode plate is a graphite electrode.

[0034] In some embodiments of the present disclosure, the cathode plate includes one of a graphite electrode, a platinum metal sheet, or a carbon fiber electrode.

[0035] In some embodiments of the present disclosure, the cathode plate is a graphite electrode.

[0036] In some embodiments of the present disclosure, the method for preparing the M-FePO4 includes: mixing the M-LiFePO4 with a lithium-containing liquid to prepare a slurry and placing it in an anode chamber while maintaining stirring, filling brine into a cathode chamber, inserting an anode plate and a cathode plate into the chamber respectively, applying power in a constant current manner until a cut-off voltage is reached, taking out the slurry from the anode chamber, filtering and collecting the solid, and obtaining the M-FePO4.

[0037] In some embodiments of the present disclosure, the lithium-containing liquid includes a lithium solution or brine.

[0038] In some embodiments of the present disclosure, the current density during power-on is 10 to 100 A / m 2 .

[0039] In some embodiments of the present disclosure, the first cut-off voltage and the second cut-off voltage are both 0.1-0.6V.

[0040] Compared with the prior art, the beneficial effects of the present invention include:

[0041] The lithium-based montmorillonite-coated LiFePO4 core-shell material provided by the present invention is obtained by coating the lithium-based montmorillonite on the surface of the LiFePO4 lithium ion sieve, and the product is a montmorillonite core-shell structure. The resistivity of the aqueous slurry prepared by the synthesized core-shell structure material is significantly reduced. The lithium-based montmorillonite-coated LiFePO4 core-shell material disclosed in the present invention is based on the principle that the interlayer ions in the montmorillonite layered structure are very easy to undergo mass-to-mass exchange. After the lithium-based montmorillonite is coated, LiFePO4 can produce a strong Li + Conductivity and excellent hydrophilicity significantly reduce the solid-liquid interface Li +Therefore, the lithium-based montmorillonite coated LiFePO4 core-shell material prepared by the present invention has a higher ion conductivity (reducing the overall resistance) and can make up for the LiFePO4-water interface Li + Defects with large conduction resistance can promote Li + The conduction between the aqueous phase and the LiFePO4 grains, that is, the overall resistivity of the slurry is reduced, and the operating voltage is lower, thereby further reducing the energy consumption of electrochemical lithium extraction from salt lakes. The lithium-based montmorillonite-coated LiFePO4 core-shell material prepared in the present disclosure can be widely used in lithium extraction from salt lake brine. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 A schematic diagram of an electrochemical lithium extraction device according to the present disclosure;

[0044] Figure 2 This is a SEM image of the lithium-based montmorillonite-coated LiFePO4 core-shell material provided in Example 1 of the present disclosure;

[0045] Figure 3 The voltage-specific capacity curves of the electrochemical devices assembled in Example 1 and Comparative Example 1 of the present disclosure are shown. DETAILED DESCRIPTION

[0046] The embodiments of the present disclosure will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments used are not specified, they are all conventional products that can be purchased commercially.

[0047] The endpoints and any values ​​of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0048] The present invention provides a lithium-montmorillonite coated LiFePO4 core-shell material, which comprises LiFePO4 as a core layer and lithium-montmorillonite as a shell layer, wherein the lithium-montmorillonite is coated on the surface of the LiFePO4, wherein the mass ratio of LiFePO4 to lithium-montmorillonite is 1:0.1% to 1%.

[0049] The present invention provides a method for preparing a lithium-based montmorillonite-coated LiFePO4 core-shell material, which comprises the following steps:

[0050] S1. Preparation of lithium montmorillonite.

[0051] The montmorillonite is mixed and infiltrated with the first lithium solution at a temperature of 70-100° C. for a time of more than 12 hours. The solid powder is then filtered and collected, and dried at a temperature of 80-120° C. for 3-12 hours to obtain the solid powder.

[0052] In the disclosure, the lithium ion concentration in the first lithium solution is greater than 1g / L, otherwise lithium montmorillonite cannot be obtained. The lithium ion concentration in the first lithium solution can be, for example, any one of 1g / L, 3g / L, 4g / L, 6g / L, 9g / L or 12g / L, or a range value between any two thereof. In the disclosure, the slurry should be kept at a temperature of 70-100°C during the stirring and infiltration process, for example, any one of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, or a range value between any two thereof. If the infiltration temperature in the disclosure is too low, fully lithiated lithium montmorillonite cannot be obtained, and if it is too high, the reaction is not easy and the lithium enhancement effect is not significant. The infiltration time should be greater than 12h. If the time is insufficient, the montmorillonite cannot be fully lithiated. The infiltration time can be, for example, any one of 12h, 14h, 15h, 16h, 18h or 24h, or a range value between any two thereof.

[0053] In the present disclosure, the drying temperature should be between 80 and 120°C, for example, it can be any one of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, or a range value between any two of them. If the drying temperature in the present disclosure is too low, sufficient drying cannot be achieved, and if the temperature is too high, the structure of the lithium montmorillonite is easily destroyed. The drying time should be between 3 and 12h, for example, it can be any one of 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, or a range value between any two of them. If the drying time in the present disclosure is too short, sufficient drying cannot be achieved, and if the time is too long, the structure of the lithium montmorillonite is easily destroyed.

[0054] S2. Mix LiFePO4 and lithium montmorillonite, add an alcohol solvent, perform a gel reaction, and dry and grind the obtained gel.

[0055] In the present disclosure, the mass ratio of LiFePO4 to lithium montmorillonite is 1:0.1% to 1%. In some typical but non-limiting embodiments, the mass ratio of LiFePO4 to lithium montmorillonite can be, for example, 1:0.1%, 1:0.2%, 1:0.3%, 1:0.4%, 1:0.5%, 1:0.6%, 1:0.7%, 1:0.8%, 1:0.9% or 1:1%, or any range between two of them, and the amount of alcohol solvent added accounts for 30% to 300% of the mass of LiFePO4.

[0056] Wherein, the alcohol solvent includes any one of ethanol, ethylene glycol, polyethylene glycol, propanol or methanol, or a combination of at least two thereof. The reaction temperature of the gel reaction is 70-100°C, for example, it can be any one of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or a range value between any two thereof. If the reaction temperature of the gel reaction in the present disclosure is too low, sufficient coating reaction cannot be achieved, and if it is too high, an uneven coating layer will be caused. The drying temperature for drying the gel should be between 80 and 120°C, for example, it can be any one of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, or The range value between any two, the drying time in the present disclosure is too low to be sufficiently dried, and too high may damage the material structure; the drying time is 1-18h, for example, it can be any one of 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h or 18h or the range value between any two, the drying time in the present disclosure is too short to be sufficiently dried, and too long will easily damage the structure of the lithium-based montmorillonite-coated LiFePO4 core-shell material.

[0057] The present invention discloses a product of montmorillonite core-shell structure obtained by coating the lithium-based montmorillonite on the surface of LiFePO4 lithium ion sieve, and the resistivity of the aqueous slurry prepared by the synthesized core-shell structure material is significantly reduced.

[0058] The lithium-based montmorillonite coated LiFePO4 core-shell material disclosed in the present invention is based on the principle that the interlayer ions in the montmorillonite layered structure are very easy to undergo mass-to-mass exchange. After the lithium-based montmorillonite is coated, it can produce a very strong Li + Conductivity and excellent hydrophilicity significantly reduce the solid-liquid interface Li + The ion conduction resistance of the embedding and extraction is thus increased by coating the LiFePO4 core-shell material with the lithium-based montmorillonite prepared in the present invention. + The conduction between the water phase and LiFePO4 grains, that is, the overall resistivity of the slurry is reduced, the operating voltage is lower, and lower energy consumption can be achieved for lithium extraction from salt lake brine.

[0059] Since the extraction of a unit amount of Li + (Q is a constant value), the theoretical operating voltage should be as small as possible, where energy consumption W = UIt = QU = QIR, U represents the applied voltage (V), I represents the current (A), R is the resistance of the electrochemical working system (Ω), t is the working time (h), and Q is the target amount of extraction Li + When the LiFePO4 electrode works in an aqueous solution, the present invention can significantly reduce the solid-liquid interface Li + Insertion and extraction ion conduction resistance, thereby reducing the actual Li + The stripping / embedding potential is improved to ultimately achieve the goal of reducing total energy consumption.

[0060] The lithium-based montmorillonite-coated LiFePO4 core-shell material prepared in the present invention can be widely used in lithium extraction from salt lake brine.

[0061] To achieve the effect of this technology, first build an electrochemical lithium extraction device, such as Figure 1 As shown, the method is verified based on this, which specifically includes the following steps:

[0062] The lithium-based montmorillonite-coated LiFePO4 core-shell material is used as a lithium ion sieve, recorded as M-LiFePO4, and a part of the lithium-based montmorillonite-coated LiFePO4 core-shell material is delithiated to prepare a lithium-poor ion sieve, recorded as M-FePO4.

[0063] The method for preparing M-FePO4 comprises: mixing M-LiFePO4 with lithium-containing liquid (lithium solution or brine) to prepare slurry, placing the slurry in an anode chamber, and stirring the mixture; filling brine in a cathode chamber; inserting an anode plate and a cathode plate into the chamber respectively; and applying electricity in a constant current mode, wherein the current density during the application of electricity is 10 to 100 A / m 2 , until the cut-off voltage reaches 0.1-0.6V, the slurry is taken out from the anode chamber and filtered to collect the solid to obtain M-FePO4.

[0064] In some typical but non-limiting embodiments, the current density when powered is 10A / m 2 , 20A / m 2 、30A / m 2 , 40A / m 2 , 50A / m 2 、60A / m 2 , 70A / m 2 、80A / m 2 、90A / m 2 or 100A / m 2The cut-off voltage may be, for example, any one of 0.1 V, 0.2 V, 0.3 V, 0.4 V, 0.5 V or 0.6 V or a range value between any two of them.

[0065] Applying it to extract lithium from salt lake brine includes the following two operations:

[0066] (1) M-LiFePO4 and M-FePO4 are added into the anode chamber and cathode chamber respectively for electrochemical lithium extraction.

[0067] (2) M-LiFePO4 and M-FePO4 are coated on the anode plate and cathode plate respectively for electrochemical lithium extraction.

[0068] Among them, scheme (1) includes the following operations:

[0069] The M-LiFePO4 and the second lithium solution are mixed and slurried and placed in the anode chamber, and the M-FePO4 and brine are mixed and slurried and placed in the cathode chamber; the main component of the second lithium solution is LiCl, and the lithium concentration is <15g / L. The solid-liquid ratio of the M-LiFePO4 and the second lithium solution is 1:1-30; the solid-liquid ratio of the M-FePO4 and brine is 1:1-30. If the solid-liquid ratio is too small, the material-plate cannot be fully contacted, and if it is too large, the current efficiency is too low.

[0070] An anode plate is inserted into the anode chamber, and a cathode plate is inserted into the cathode chamber. The anode chamber and the cathode chamber are separated by an anion membrane. Voltage is applied to the anode plate and the cathode plate to perform electrochemical lithium extraction. The operation stops when the cut-off voltage (0.1-0.6V) is reached.

[0071] The anode chamber and the cathode chamber are stirred during the lithium extraction process. The stirring speed is 100-1000 r / min, for example, any one of 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min or a range between any two thereof.

[0072] In solution (2):

[0073] The coating thickness of M-LiFePO4 is 0.01 to 1 cm; the coating thickness of M-FePO4 is 0.01 to 1 cm.

[0074] The anode plate and cathode plate used in solution (1) or solution (2) can be universal. Specifically, the anode plate includes one of a graphite electrode, a platinum metal sheet or a carbon fiber electrode; preferably, the anode plate is a graphite electrode. The cathode plate includes one of a graphite electrode, a platinum metal sheet or a carbon fiber electrode; preferably, the cathode plate is a graphite electrode.

[0075] The lithium-based montmorillonite-coated LiFePO4 core-shell material provided by the present invention has a high ion conductivity (reducing the overall resistance) and can compensate for the LiFePO4-water interface Li + The defect of large conduction resistance can significantly reduce the working voltage of electrochemical lithium extraction, thereby further reducing the energy consumption of electrochemical lithium extraction from salt lakes.

[0076] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0077] The concentrations of the main elements in the salt lake brine used in the embodiments and comparative examples provided in the present disclosure are all referred to Table 1:

[0078] Table 1. Concentrations of major elements in salt lake brine

[0079]

[0080]

[0081] Example 1

[0082] Step S1, preparation of lithium-based montmorillonite: taking commercial montmorillonite as raw material, soaking it in a solution with a lithium concentration of 3 g / L, keeping it at 80° C. and stirring it for 16 hours, then filtering and collecting the obtained solid powder, and drying it at 100° C. for 6 hours to obtain lithium-based montmorillonite;

[0083] Step S2, preparing lithium montmorillonite coated LiFePO4 core-shell material: using commercial LiFePO4 as raw material, the lithium montmorillonite obtained in step 1 is mixed with it at a mass ratio of 0.2%, and ethanol is added according to 30% of the mass of LiFePO4, and a sol-gel reaction is carried out at 100°C. After the above gel is evaporated, it is dried at 80°C for 18h and ground evenly to obtain Figure 2 The lithium-based montmorillonite-coated LiFePO4 core-shell material (abbreviated as M-LiFePO4) shown;

[0084] Step S3, preparation of lithium-poor ion sieve material: M-LiFePO4 prepared in step S2 and lithium chloride solution with a lithium concentration of 1g / L were mixed in a liquid-solid ratio of 2:1 to prepare a slurry, which was placed in the anode chamber and stirred at 100r / min. Brine was filled in the cathode chamber, and graphite electrodes were inserted into the chamber as anode plates and cathode plates, respectively. The anode plates and cathode plates were charged at 20A / m 2The electric current was supplied in a constant current mode until the cut-off voltage reached 0.3 V, and the slurry was taken out from the anode chamber and filtered to collect the solid, which was named as the lithium-poor ion sieve material (M-FePO4);

[0085] Step S4, electrochemical lithium extraction: M-LiFePO4 in step S2 and lithium chloride solution with a lithium concentration of 5g / L are mixed in a liquid-solid ratio of 5:1 to prepare a slurry and placed in the anode chamber; M-FePO4 in step S3 and brine are mixed in a ratio of 5:1 to prepare a slurry and placed in the cathode chamber; a graphite electrode and a graphite electrode are inserted into the chamber as the anode plate and the cathode plate, respectively; the two chambers are stirred at 100r / min, separated by an anion membrane, and the cathode and anode are connected to an external power supply at 20A / m 2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.3V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0086] Example 2

[0087] Step S1, preparation of lithium-based montmorillonite: taking commercial montmorillonite as a raw material, soaking it in a solution with a lithium concentration of 6 g / L, keeping it at 70° C. and stirring it for 14 hours, then filtering and collecting the obtained solid powder, and drying it at 80° C. for 12 hours, that is, lithium-based montmorillonite;

[0088] Step S2, preparing lithium-montmorillonite-coated LiFePO4 core-shell material: using commercial LiFePO4 as a raw material, mixing the lithium-montmorillonite obtained in step 1 with it at a mass ratio of 0.1%, and adding polyethylene glycol at 300% of the mass of LiFePO4 to carry out a sol-gel reaction at 80°C, after the above gel is evaporated to dryness, drying it at 120°C for 1h and grinding it evenly to obtain a lithium-montmorillonite-coated LiFePO4 core-shell material (referred to as M-LiFePO4);

[0089] Step S3, preparation of lithium-poor ion sieve material: M-LiFePO4 prepared in step S2 and lithium chloride solution with a lithium concentration of 2g / L were mixed in a liquid-solid ratio of 6:1 to prepare a slurry, which was placed in the anode chamber and stirred at 1000r / min. Brine was filled in the cathode chamber, and platinum metal sheets and platinum metal sheets were inserted into the chamber as anode plates and cathode plates, respectively. The anode plate and cathode plate were stirred at 10A / m 2 The electricity was supplied in a constant current mode until the cut-off voltage reached 0.6 V, and the slurry was taken out from the anode chamber and filtered to collect the solid, which was named as the lithium-poor ion sieve material (M-FePO4);

[0090] Step S4, electrochemical lithium extraction: M-LiFePO4 in step S2 and lithium chloride solution with a lithium concentration of 1g / L are mixed in a liquid-solid ratio of 5:1 to prepare a slurry and placed in the anode chamber; M-FePO4 in step S3 and brine are mixed in a ratio of 5:1 to prepare a slurry and placed in the cathode chamber; a graphite electrode and a platinum metal sheet are inserted into the chamber as the anode plate and the cathode plate respectively; the two chambers are stirred at 400r / min, separated by an anion membrane, and the cathode and the anode are connected to an external power supply at 10A / m 2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.6V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0091] Example 3

[0092] Step S1, preparation of lithium-based montmorillonite: taking commercial montmorillonite as raw material, soaking it in a solution with a lithium concentration of 1 g / L, keeping it at 100° C. and stirring it for 24 hours, then filtering and collecting the obtained solid powder, and drying it at 80° C. for 9 hours, which is lithium-based montmorillonite;

[0093] Step S2, preparing lithium-montmorillonite-coated LiFePO4 core-shell material: using commercial LiFePO4 as a raw material, mixing the lithium-montmorillonite obtained in step 1 with it at a mass ratio of 0.6%, and adding ethylene glycol at 200% of the mass of LiFePO4 at 70°C for sol-gel reaction, after the above gel is evaporated, it is dried at 100°C for 6h and ground evenly to obtain lithium-montmorillonite-coated LiFePO4 core-shell material (referred to as M-LiFePO4);

[0094] Step S3, preparation of lithium-poor ion sieve material: M-LiFePO4 prepared in step S2 and lithium chloride solution with a lithium concentration of 6 g / L were mixed in a liquid-solid ratio of 10:1 to prepare a slurry, which was placed in the anode chamber and stirred at 200 r / min. Brine was filled in the cathode chamber, and carbon fiber electrode sheets and carbon fiber electrode sheets were inserted into the chamber as anode plates and cathode plates, respectively. The mixture was stirred at 100 A / m 2 The electricity was supplied in a constant current mode until the cut-off voltage reached 0.1 V, and the slurry was taken out from the anode chamber and filtered to collect the solid, which was named as the lithium-poor ion sieve material (M-FePO4);

[0095] Step S4, electrochemical lithium extraction: M-LiFePO4 in step S2 and lithium chloride solution with a lithium concentration of 3g / L are mixed in a liquid-solid ratio of 20:1 to prepare a slurry and placed in the anode chamber; M-FePO4 in step S3 and brine are mixed in a ratio of 20:1 to prepare a slurry and placed in the cathode chamber; a carbon fiber electrode sheet and a carbon fiber electrode sheet are inserted into the chamber as the anode plate and the cathode plate respectively; the two chambers are stirred at 600r / min, separated by an anion membrane, and the cathode and anode are connected to an external power supply at 100A / m 2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.1V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0096] Example 4

[0097] Step S1, preparation of lithium-based montmorillonite: taking commercial montmorillonite as a raw material, soaking it in a solution with a lithium concentration of 12 g / L, keeping it at 90° C. and stirring it for 12 hours, then filtering and collecting the obtained solid powder, and drying it at 90° C. for 9 hours to obtain lithium-based montmorillonite;

[0098] Step S2, preparing lithium-montmorillonite-coated LiFePO4 core-shell material: using commercial LiFePO4 as a raw material, mixing the lithium-montmorillonite obtained in step 1 with it at a mass ratio of 0.6%, and adding propanol at 150% of the mass of LiFePO4 to carry out a sol-gel reaction at 100° C., after the above gel is evaporated to dryness, it is dried at 90° C. for 9 hours and ground evenly to obtain a lithium-montmorillonite-coated LiFePO4 core-shell material (referred to as M-LiFePO4);

[0099] Step S3, preparation of lithium-poor ion sieve material: M-LiFePO4 prepared in step S2 and lithium chloride solution with a lithium concentration of 9g / L were mixed in a liquid-solid ratio of 12:1 to prepare a slurry, which was placed in the anode chamber and stirred at 100r / min. Brine was filled in the cathode chamber, and graphite electrodes were inserted into the chamber as anode plates and cathode plates, respectively. The anode plates and cathode plates were charged at 60A / m 2 The electricity was supplied in a constant current mode until the cut-off voltage reached 0.4 V, and the slurry was taken out from the anode chamber and filtered to collect the solid, which was named as the lithium-poor ion sieve material (M-FePO4);

[0100] Step S4, electrochemical lithium extraction: M-LiFePO4 in step S2 and lithium chloride solution with a lithium concentration of 10g / L are mixed in a liquid-solid ratio of 10:1 to prepare a slurry and placed in the anode chamber; M-FePO4 in step S3 and brine are mixed in a ratio of 10:1 to prepare a slurry and placed in the cathode chamber; a graphite electrode and a graphite electrode are inserted into the chamber as the anode plate and the cathode plate respectively; the two chambers are stirred at 900r / min, separated by an anion membrane, and the cathode and anode are connected to an external power supply at 30A / m2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.6V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0101] Example 5

[0102] Step S1, taking commercial montmorillonite as a raw material, immersing it in a lithium solution with a concentration of 4 g / L, keeping it at 90° C. and stirring it for 18 hours, then filtering and collecting the obtained solid powder, and drying it at 120° C. for 3 hours, to obtain lithium-based montmorillonite;

[0103] Step S2, preparing lithium-montmorillonite-coated LiFePO4 core-shell material: using commercial LiFePO4 as a raw material, mixing the lithium-montmorillonite obtained in step 1 with it at a mass ratio of 1%, and adding methanol at 250% of the mass of LiFePO4 to carry out a sol-gel reaction at 90° C., after the above gel is evaporated to dryness, it is dried at 110° C. for 3 hours and ground evenly to obtain a lithium-montmorillonite-coated LiFePO4 core-shell material (referred to as M-LiFePO4);

[0104] Step S3, preparation of lithium-poor ion sieve material: M-LiFePO4 prepared in step S2 and lithium chloride solution with a lithium concentration of 12 g / L were mixed in a liquid-solid ratio of 16:1 to prepare a slurry, which was placed in the anode chamber and stirred at 300 r / min. Brine was filled in the cathode chamber, and graphite electrodes were inserted into the chamber as anode plates and cathode plates, respectively. The anode plates and cathode plates were stirred at 30 A / m. 2 The electricity was supplied in a constant current mode until the cut-off voltage reached 0.6 V, and the slurry was taken out from the anode chamber and filtered to collect the solid, which was named as the lithium-poor ion sieve material (M-FePO4);

[0105] Step S4, electrochemical lithium extraction: M-LiFePO4 in step S2 and lithium chloride solution with a lithium concentration of 12g / L are mixed in a liquid-solid ratio of 2:1 to prepare a slurry and placed in the anode chamber; M-FePO4 in step S3 is mixed in a slurry of 2:1 with brine and placed in the cathode chamber; a graphite electrode is inserted into the chamber and a graphite electrode is used as an anode plate and a cathode plate respectively; both chambers are stirred at 1000r / min, separated by an anion membrane, and an external power supply is connected to the cathode and anode at 100A / m 2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.6V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0106] Example 6

[0107] Step S1, taking commercial montmorillonite as a raw material, immersing it in a solution with a lithium concentration of 9 g / L, keeping it at 100° C. and stirring it for 15 hours, then filtering and collecting the obtained solid powder, and drying it at 120° C. for 12 hours, to obtain lithium-based montmorillonite;

[0108] Step S2, preparing lithium-montmorillonite-coated LiFePO4 core-shell material: using commercial LiFePO4 as a raw material, mixing the lithium-montmorillonite obtained in step 1 with it at a mass ratio of 0.3%, and adding ethanol at 180% of the mass of LiFePO4 at 85°C for sol-gel reaction, after the above gel is evaporated, it is dried at 90°C for 12h and ground evenly to obtain lithium-montmorillonite-coated LiFePO4 core-shell material (abbreviated as M-LiFePO4);

[0109] Step S3, preparation of lithium-poor ion sieve material: M-LiFePO4 prepared in step S2 and lithium chloride solution with a lithium concentration of 15 g / L were mixed in a liquid-solid ratio of 20:1 to prepare a slurry, which was placed in the anode chamber and stirred at 500 r / min. Brine was filled in the cathode chamber, and platinum metal sheets and platinum metal sheets were inserted into the chamber as anode plates and cathode plates, respectively. The anode plate and cathode plate were stirred at 50 A / m. 2 The electric current was supplied in a constant current mode until the cut-off voltage reached 0.3 V, and the slurry was taken out from the anode chamber and filtered to collect the solid, which was named as the lithium-poor ion sieve material (M-FePO4);

[0110] Step S4, electrochemical lithium extraction: M-LiFePO4 in step S2 and lithium chloride solution with a lithium concentration of 15g / L are mixed in a liquid-solid ratio of 9:1 to prepare a slurry and placed in the anode chamber; M-FePO4 in step S3 and brine are mixed in a ratio of 9:1 to prepare a slurry and placed in the cathode chamber; platinum metal sheets and platinum metal sheets are inserted into the chamber as anode plates and cathode plates respectively; both chambers are stirred at 300r / min, separated by an anion membrane, and the cathode and anode are connected to an external power supply at 60A / m 2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.1V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0111] Example 7

[0112] Steps S1-S3 are the same as those in Example 1.

[0113] Step S4, electrochemical lithium extraction: the M-LiFePO4 in step S2 is coated on the anode plate with a coating thickness of 0.1 cm, and the M-FePO4 in step S3 is coated on the cathode plate with a coating thickness of 0.1 cm, and the anode plate coated with M-LiFePO4 and the cathode plate coated with M-FePO4 are inserted into the chamber, and lithium solution is introduced into the anode chamber, and brine is introduced into the cathode chamber. Both chambers are stirred at 100 r / min, separated by an anion membrane, and the cathode and anode are connected to an external power supply at 20 A / m 2 Electrochemical lithium extraction is performed and the work stops when the cut-off voltage reaches 0.3V. + It is extracted by M-FePO4 and released in the anode chamber. The anode chamber solution is collected by filtration to obtain lithium-rich solution.

[0114] Comparative Example 1

[0115] The difference from Example 1 is that step S1 and step S2 are not performed, and commercial LiFePO4 material is directly used to prepare a lithium-poor ion sieve, and then electrochemical lithium extraction is performed.

[0116] Comparative Example 2

[0117] The difference from Example 1 is that in step S1, the commercial montmorillonite material is not subjected to lithiation treatment, but the LiFePO4 material is directly coated with the commercial montmorillonite, and then electrochemical lithium extraction is performed.

[0118] Comparative Example 3

[0119] The difference from Example 1 is that the infiltration temperature in step S1 is too high, and the infiltration is carried out at 120° C. with stirring for 16 hours.

[0120] Comparative Example 4

[0121] The difference from Example 1 is that the drying temperature in step S1 is too high, and the drying is performed at 150° C. for 6 hours.

[0122] Comparative Example 5

[0123] The difference from Example 1 is that the mass ratio of lithium-based montmorillonite and LiFePO4 materials used in step S2 is too small, and they are mixed at 0.01%, and then other steps are performed for electrochemical lithium extraction.

[0124] Comparative Example 6

[0125] The difference from Example 1 is that the mass ratio of lithium-based montmorillonite to LiFePO4 material used in step S2 is too large, and they are mixed at 2%, and then other steps are performed to electrochemically extract lithium.

[0126] Comparative Example 7

[0127] The difference from Example 1 is that the ethanol used in step S2 is replaced by pure water, and then other steps are performed to electrochemically extract lithium.

[0128] Comparative Example 8

[0129] The difference from Example 1 is that step S1 is not performed, and the lithium-based montmorillonite used in step S2 is replaced by lithium mica mineral.

[0130] Comparative Example 9

[0131] The difference from Example 1 is that the LiFePO4 used in step S2 is replaced by LiCoO2.

[0132] Experimental Example 1

[0133] The slurry conductivity of the lithium ion sieve provided in the above-mentioned embodiments 1-7 and comparative examples 1-9 is measured when the slurry is slurried, and the slurry conductivity detection method includes a slurry resistance test system. Please refer to Table 2 for the detection results.

[0134] Table 2. Statistical table of slurry conductivity of lithium ion sieves in various examples during slurry preparation

[0135] Example Slurry conductivity (S / m) Example 1 0.92 Example 2 0.79 Example 3 0.84 Example 4 0.75 Example 5 0.88 Example 6 0.91 Example 7 0.78 Comparative Example 1 0.21 Comparative Example 2 0.25 Comparative Example 3 0.27 Comparative Example 4 0.28 Comparative Example 5 0.30 Comparative Example 6 0.31 Comparative Example 7 0.26 Comparative Example 8 0.29 Comparative Example 9 0.62

[0136] As can be seen from the above table, in Comparative Example 1, LiFePO4 material is directly used to prepare the lithium-poor ion sieve without coating it, and its slurry conductivity is significantly lower than that of Example 1 and other comparative examples. In Comparative Example 2, montmorillonite is directly used to coat the LiFePO4 material. At this time, since montmorillonite is not coated with lithium, its Li + The conductivity and hydrophilicity are significantly reduced, so the conductivity of the slurry prepared by it is slightly higher than that of Comparative Example 1, but still significantly lower than that of Example 1. It can be seen from the data of Comparative Examples 3-6 that when the parameters such as the mass ratio of infiltration, drying and coating exceed the scope of the present disclosure, it will cause the conductivity of the slurry to be significantly reduced, and it can be seen from the data of Comparative Example 7 that pure water is used instead of ethanol. Under the same conditions, pure water is not easy to volatilize, resulting in excessive water content in the gel, which is not conducive to subsequent drying, and thus causing the conductivity of Comparative Example 7 to be significantly lower than that of Example 1, which fully proves that not all solvents can be used to mix LiFePO4 and lithium-based montmorillonite. It can be seen from the data of Comparative Example 8 that when other lithium-containing minerals are selected, its conductivity is still significantly lower than that of Example 1, because hectorite has a higher ionic conductivity. It can be seen from the data of Comparative Example 9 that when other positive electrode materials are selected as the core, its slurry conductivity is poor, mainly due to the high conduction starting voltage of LiCoO2, which leads to its conductivity still significantly lower than that of Example 1. Moreover, the dissolution rate of lithium cobalt oxide is relatively high, and it may reach more than 30% after power is turned on. 2+ and Li +Therefore, the conductivity of the slurry prepared by the lithium-based montmorillonite-coated LiFePO4 core-shell material provided in the embodiment of the present disclosure is significantly greater than that of the LiFePO4 slurry of other comparative examples.

[0137] Experimental Example 2

[0138] The charge and discharge medium pressure and the power consumption required to extract 1 kg of lithium were tested for the electrochemical extraction of lithium by the lithium ion sieves provided in the above Examples 1-7 and Comparative Examples 1-9. Figure 3 and Table 3:

[0139] Table 3. Statistics of charging and discharging medium voltage, specific capacity and power consumption required to extract 1kg of lithium for each example

[0140]

[0141]

[0142] It can be seen from the above table that to achieve the same level of specific capacity (~80mAh / g), the embodiments all have a lower charging and discharging medium voltage than the comparative example, wherein the embodiments are optimized for lithium-based montmorillonite coating, while the comparative example is not coated or coated with other materials, so the lithium-based montmorillonite-coated LiFePO4 core-shell material has lower energy consumption for extracting lithium per unit mass.

[0143] In summary, the lithium-based montmorillonite-coated LiFePO4 core-shell material provided by the present invention is obtained by coating the lithium-based montmorillonite on the surface of the LiFePO4 lithium ion sieve, and the product is a montmorillonite core-shell structure. The resistivity of the aqueous slurry prepared by the synthesized core-shell structure material is significantly reduced. The lithium-based montmorillonite-coated LiFePO4 core-shell material disclosed in the present invention is based on the principle that the interlayer ions in the montmorillonite layered structure are very easy to undergo mass-to-mass substitution. After the lithium-based montmorillonite is coated, LiFePO4 can produce a strong Li + Conductivity and excellent hydrophilicity significantly reduce the solid-liquid interface Li + Therefore, the lithium-based montmorillonite coated LiFePO4 core-shell material prepared by the present invention has a higher ion conductivity (reducing the overall resistance) and can make up for the LiFePO4-water interface Li + Defects with large conduction resistance can promote Li + The conduction between the aqueous phase and the LiFePO4 grains, that is, the overall resistivity of the slurry is reduced, and the operating voltage is lower, thereby further reducing the energy consumption of electrochemical lithium extraction from salt lakes. The lithium-based montmorillonite-coated LiFePO4 core-shell material prepared in the present disclosure can be widely used in lithium extraction from salt lake brine.

[0144] The optional implementation modes of the present disclosure are described in detail above, but the present disclosure is not limited thereto. Within the technical concept of the present disclosure, the technical solution of the present disclosure can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present disclosure and belong to the protection scope of the present disclosure.

[0145] Industrial Applicability

[0146] The lithium-based montmorillonite-coated LiFePO4 core-shell material provided by the present invention is obtained by coating the lithium-based montmorillonite on the surface of the LiFePO4 lithium ion sieve, and the product is a montmorillonite core-shell structure. The resistivity of the aqueous slurry prepared by the synthesized core-shell structure material is significantly reduced. The lithium-based montmorillonite-coated LiFePO4 core-shell material disclosed in the present invention is based on the principle that the interlayer ions in the montmorillonite layered structure are very easy to undergo mass-to-mass exchange. After the lithium-based montmorillonite is coated, LiFePO4 can produce a strong Li + Conductivity and excellent hydrophilicity significantly reduce the solid-liquid interface Li + Therefore, the lithium-based montmorillonite coated LiFePO4 core-shell material prepared by the present invention has a higher ion conductivity (reducing the overall resistance) and can make up for the LiFePO4-water interface Li + Defects with large conduction resistance can promote Li + The conduction between the aqueous phase and the LiFePO4 grains, that is, the overall resistivity of the slurry is reduced, and the operating voltage is lower, thereby further reducing the energy consumption of electrochemical lithium extraction from salt lakes. The lithium-based montmorillonite-coated LiFePO4 core-shell material prepared in the present disclosure can be widely used in lithium extraction from salt lake brine.

Claims

1. A lithium-based montmorillonite-coated LiFePO4 core-shell material, characterized in that: It includes LiFePO4 as a core layer and lithium-based montmorillonite as a shell layer, and the lithium-based montmorillonite is coated on the surface of the LiFePO4; The mass ratio of the LiFePO4 to the lithium montmorillonite is 1:0.1%~1%; the preparation method of the lithium montmorillonite-coated LiFePO4 core-shell material comprises mixing LiFePO4 and lithium montmorillonite, adding an alcohol solvent, performing a gel reaction, and drying and grinding the obtained gel; The preparation method of the lithium-based montmorillonite comprises: mixing and infiltrating the montmorillonite with a first lithium solution, wherein the infiltration temperature is 70-100° C., the infiltration time is greater than 12 hours, then filtering and collecting the solid powder, and drying at 80-120° C. for 3-12 hours; the alcohol solvent comprises any one of ethanol, ethylene glycol, polyethylene glycol, propanol or methanol, or a combination of at least two thereof.

2. A method for preparing a lithium-based montmorillonite-coated LiFePO4 core-shell material, characterized in that: The method comprises mixing LiFePO4 and lithium montmorillonite, adding an alcohol solvent, carrying out a gel reaction, and drying and grinding the obtained gel; The mass ratio of the LiFePO4 to the lithium-based montmorillonite is 1:0.1%~1%; The preparation method of the lithium-based montmorillonite comprises: mixing and infiltrating the montmorillonite with a first lithium solution, wherein the infiltration temperature is 70-100° C. and the infiltration time is greater than 12 hours, then filtering and collecting the solid powder, and drying at 80-120° C. for 3-12 hours to obtain the solid powder; The alcohol solvent includes any one of ethanol, ethylene glycol, polyethylene glycol, propanol or methanol, or a combination of at least two thereof.

3. The method for preparing the lithium-based montmorillonite-coated LiFePO4 core-shell material according to claim 2, characterized in that: The added amount of the alcohol solvent accounts for 30%-300% of the mass of the LiFePO4.

4. The method for preparing the lithium-based montmorillonite-coated LiFePO4 core-shell material according to claim 2, characterized in that: The temperature of the gel reaction is 70-100°C.

5. The method for preparing the lithium-based montmorillonite-coated LiFePO4 core-shell material according to claim 2, characterized in that: The gel is dried at a temperature of 80-120° C. and a drying time of 1-18 hours.

6. The method for preparing the lithium-based montmorillonite-coated LiFePO4 core-shell material according to claim 2, characterized in that: The lithium ion concentration in the first lithium solution is greater than 1 g / L.

7. Application of the lithium-based montmorillonite-coated LiFePO4 core-shell material prepared by the preparation method of the lithium-based montmorillonite-coated LiFePO4 core-shell material as claimed in any one of claims 2 to 6 in lithium extraction from salt lake brine.

8. A method for extracting lithium from salt lake brine, characterized in that: It includes: The lithium-based montmorillonite-coated LiFePO4 core-shell material as claimed in claim 1 or the lithium-based montmorillonite-coated LiFePO4 core-shell material prepared by the preparation method of the lithium-based montmorillonite-coated LiFePO4 core-shell material as claimed in any one of claims 2 to 6 is used as a lithium ion sieve, recorded as M-LiFePO4, and a part of the lithium-based montmorillonite-coated LiFePO4 core-shell material is delithiated to prepare a lithium-poor ion sieve, recorded as M-FePO4; The M-LiFePO4 and the M-FePO4 are respectively added into the anode chamber and the cathode chamber for electrochemical lithium extraction; or, The M-LiFePO4 and the M-FePO4 are coated on the anode plate and the cathode plate respectively for electrochemical lithium extraction.

9. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: When the M-LiFePO4 and the M-FePO4 are added to the anode chamber and the cathode chamber respectively for electrochemical lithium extraction, the following operations are included: The M-LiFePO4 and the second lithium solution are mixed into a slurry and placed in the anode chamber, and the M-FePO4 and brine are mixed into a slurry and placed in the cathode chamber; An anode plate is inserted into the anode chamber, and a cathode plate is inserted into the cathode chamber. The anode chamber and the cathode chamber are separated by an anion membrane. Voltage is applied to the anode plate and the cathode plate to perform electrochemical lithium extraction, and the operation stops when a first cut-off voltage is reached.

10. The method for extracting lithium from salt lake brine according to claim 9, characterized in that: The solid-liquid ratio of the M-LiFePO4 and the second lithium solution in slurry preparation is 1:1-30; the solid-liquid ratio of the M-FePO4 and the brine in slurry preparation is 1:1-30.

11. The method for extracting lithium from salt lake brine according to claim 9, characterized in that: The anode chamber and the cathode chamber are kept stirred during the lithium extraction process.

12. The method for extracting lithium from salt lake brine according to claim 11, characterized in that: The stirring speed is 100-1000r / min.

13. The method for extracting lithium from salt lake brine according to claim 9, characterized in that: The main component of the second lithium solution is LiCl, wherein the lithium concentration is <15g / L.

14. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: When the M-LiFePO4 and the M-FePO4 are coated on the anode plate and the cathode plate respectively for electrochemical lithium extraction, the coating thickness of the M-LiFePO4 is 0.01-1 cm; the coating thickness of the M-FePO4 is 0.01-1 cm.

15. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: The anode plate includes one of a graphite electrode, a platinum metal sheet or a carbon fiber electrode.

16. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: The anode plate is a graphite electrode.

17. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: The cathode plate includes one of a graphite electrode, a platinum metal sheet or a carbon fiber electrode.

18. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: The cathode plate is a graphite electrode.

19. The method for extracting lithium from salt lake brine according to claim 8, characterized in that: The method for preparing the M-FePO4 includes: mixing the M-LiFePO4 with a lithium-containing liquid to prepare a slurry, placing the slurry in an anode chamber, and maintaining stirring, filling brine into a cathode chamber, inserting an anode plate and a cathode plate into the chamber respectively, and applying electricity in a constant current manner until a second cut-off voltage is reached, taking out the slurry from the anode chamber, filtering and collecting the solid, and obtaining the M-FePO4.

20. The method for extracting lithium from salt lake brine according to claim 19, characterized in that: The lithium-containing liquid includes a lithium solution or brine.

21. The method for extracting lithium from salt lake brine according to claim 19, characterized in that: The current density during power on is 10-100A / m 2 .

22. The method for extracting lithium from salt lake brine according to claim 19, characterized in that: The first cut-off voltage and the second cut-off voltage are both 0.1-0.6V.

Citation Information

Patent Citations

  • Lithium extraction with coated ion exchange particles

    CN110139712A

  • Electrode material for salt lake lithium extraction and preparation method and application of thereof

    CN113278820A